Merajut Mimpi Melalui Pelatihan Merajut: Pemberdayaan Ekonomi PKK Kapanewon Ngemplak Sleman - Sutrisno Sutrisno; Muchsin Muthohar; Yazid (Rahmatan Lil 'Alamin Journal of Community Services, 2022)
One of the missions of the Ngemplak sub-district is to increase human resources and build a creative and innovative economy. For this reason, community empowerment is needed in order to improve living standards. The purpose of community service carried out by the UII Faculty of Business & Economics Management Development Center is to provide training on making knitting crafts to PKK mothers, Ngemplak District. This activity collaborated with the Ngemplak District UKMK Forum as a forum that accommodates MSME activities as well as providing guidance. The UMKM Communication Forum (Forkom) is an institution that helps sub-districts and drives MSMEs at the sub-district level. 25 training participants were representatives from 5 sub-districts, each of whom sent 5 participants. Prior to the training, participants were provided with entrepreneurship material, production management, and marketing of knitting products. The training was given for 2 weeks with four face-to-face meetings. The results of the training were very satisfying, because each participant was able to practice the training material even though the results were not evenly distributed. The UMKM Forum continues to provide assistance in both production and marketing to participants after the completion of the training program so that participants' expertise is maintained.